Instituto de estudos superiores do Maranhão - iesma: origem histórico-educacional - Sousa, Ana Lúcia Pinheiro Silva (2022)
This academic work emphasized the relations between the Catholic Church of São Luís of Maranhão and the local political and economic powers in the offer of higher education and in the control of the educational field, in contradiction with the secular state, proclaimed in the first constitution of the Republic. To understand this relationship, this one addressed the topic of the creation of confessional higher education institutions in Brazil and the religious formation in São Luís, beginning with the creation of a confessional higher institution, the University (Catholic) of Maranhão - UMA, giving rise to the Federal University of Maranhão – UFMA, and the history of the management of the Archbishop of São Luís, Dom José de Medeiros Delgado, leader of this process. This paper wonders the reason why, even having been founder and leader by the Sociedade Maranhese de Cultura Superior - SOMACS – the keeper of that University, before its federalization, in 1966, the local Church has not managed to create in it the desired course of theology for priestly formation. This dissertation ends with the history of the creation of IESMA, which took place under the SOMACS, after some years of inactivity. In 1976, with the creation of the institute, the new history of the church began with regard to the dreamed and idealized course of Theology. It raises the main question of the original project of this dissertation: why, even with so much influence and power in the educational field, the Catholic Church of São Luis of Maranhão would never have been able to create a theology course while its institutions were linked and were, to a large extent, partly financed by the government? Is the secular state capable of explaining this defeat of the Church? This question opens the present work to future researches.